Chemogenetic control of nanobodies - Farrants, Helen; Tarnawski, Miroslaw; Müller, Thorsten G.; Otsuka, Shotaro; Hiblot, Julien; Koch, Birgit; Kueblbeck, Moritz; Kräusslich, Hans-Georg; Ellenberg, Jan; Johnsson, Kai (Nature methods, 2020)
We introduce an engineered nanobody whose affinity to green fluorescent protein (GFP) can be switched on and off with small molecules. By controlling the cellular localization of GFP fusion proteins, the engineered nanobody allows interrogation of their roles in basic biological processes, an approach that should be applicable to numerous previously described GFP fusions. We also outline how the binding affinities of other nanobodies can be controlled by small molecules.
Gesehen am 13.01.2021